DIAGNOSIS KESULITAN BELAJAR MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH PADA MATA KULIAH PEMBELAJARAN IPA DI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Muslimatul Hairiah; Muhammad Yaumi; Safe Safe; Fajri Basam (JIPMI (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah), 2022)
This paper is the result of research that discusses the diagnosis of learning difficulties for students ofMadrasah Ibtidaiyah teacher education in science learning courses at the Tarbiyah and TeacherTraining Faculty of UIN Alauddin Makassar. This study has the objectives to: 1) describe the formof learning difficulties for madrasah ibtidaiyah teacher education students in science learning coursesat the tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar, 2) provide solutions inovercoming learning difficulties for madrasah ibtidaiyah teacher education students in sciencelearning courses at Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. The typeof research used is Descriptive qualitative, the subject of this research is ten students of madrasahibtidaiyah teacher education. The results of the descriptive research show that the difficulty inunderstanding the science material itself is still lacking, besides that the facilities in studying scienceare still inadequate. Then the factors of learning difficulties are students understanding of sciencematerial which is still lacking, pratikum implementation is still not implemented, and learningmethods are still less effective. And the solution in overcoming learning difficulties is that lecturersshould always provide motivation to students who have difficulty learning science, lecturers shouldalso provide training to read scientific terms and provide guidance on how to use laboratories, sciencelaboratory facilities majoring in madrasah ibtidaiyah teacher education at the Tarbiyah andTeacher Training Faculty UIN Alauddin Makassar was held.